LEGAL PROTECTION TO THE INDONESIAN MIGRANT WORKERS IN THE PERSPECTIVE OF HUMAN RIGHTS - Mihardi, Raden Muhammad (Advances in Social Sciences Research Journal, 2020)
Purpose of the study: This research aims to describe legal issue related to the protection to Indonesian migrant workers who work abroad and to analyze the existence of migrant workers in Indonesia, viewed from human rights which must get legal protection in constitution and regulation of legal norm and implementation in the applicable legislation. Methodology: This research used the normative research methodology supported by empirical data from the document of institutional study. Main Findings: Research about the protection of human rights in Indonesian Migrant Worker sector is a certainty. It is guaranteed in the international documents (Declaration of Human Rights in the United Nations, Convention of United Nations on Ecosoc and ILO Convention) and national documents (1945 Constitution and Law of Indonesian Migrant Worker Protection). However, in the perspective of its implementation, it has complexity. The protection to Indonesian migrant workers involves many parties, central and regional rules, and culture. This research focuses on the context of Indonesian Migrant Worker protection in a country where they work from the perspective of human rights. This research has novelty since it captures and analyzes issue of Indonesian Migrant Worker in rules and empirical terms based on the database. Applications of this study: this study can be useful for Immigration is one of the instruments to support unity of family with different nationality background. Novelty/Originality of this study: The new in this study that may find the ideal concept of the treasury of jurisprudence, particularly for foreign citizens who legally get married with Indonesian citizens and ex-Indonesian citizens and children born from legitimate mixed marriage with double citizenship.